Involving community in genes and pathway curation. (16th January 2019) - Naithani, Sushma; Gupta, Parul; Preece, Justin; Garg, Priyanka; Fraser, Valerie; Padgitt-Cobb, Lillian K; Martin, Matthew; Vining, Kelly; Jaiswal, Pankaj
Abstract: Biocuration plays a crucial role in building databases and complex systems-level platforms required for processing, annotating and analyzing 'Big Data' in biology. However, biocuration efforts cannot keep pace with a dramatic increase in the production of omics data; this presents one of the bottlenecks in genomics. In two pathway curation jamborees, Plant Reactome curators tested strategies for introducing researchers to pathway curation tools, harnessing biologists' expertise in curating plant pathways and developing a network of community biocurators. We summarize the strategy, workflow and outcomes of these exercises, and discuss the role of community biocuration in advancing databases and genomic resources.